2013
DOI: 10.1590/s1677-5538.ibju.2013.03.18
|View full text |Cite
|
Sign up to set email alerts
|

Leiomyoma of the urinary bladder: a case report

Abstract: The case of a 71-year-old woman who presented with one year history of pelvic pain and occasional dysuria is reported. Computed tomography and Magnetic Resonance Imaging revealed a well defined intramural bladder mass. The histological findings of the surgical specimen confirmed a leiomyoma of the urinary bladder. The clinical presentation, imaging findings and management of this relatively rare benign tumor are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 2 publications
0
4
1
Order By: Relevance
“…Several endocrine alterations and genomic mutations have been associated with an increased risk of bladder leiomyoma [10,11]; however, our patient did not screen positive for any of them.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Several endocrine alterations and genomic mutations have been associated with an increased risk of bladder leiomyoma [10,11]; however, our patient did not screen positive for any of them.…”
Section: Discussioncontrasting
confidence: 75%
“…The treatment, which is almost always surgical, is strongly associated with the tumour burden, and range from TURB for smaller tumours to open surgical excision or radical cystectomy for larger ones. Minimally invasive surgeries, such as laparoscopic surgery and robot-assisted excision, have been described as well [10,[23][24][25][26][27]. Also given the young age of the patient, an extremely accurate preoperative diagnosis was of utmost importance to plan the most conservative treatment.…”
Section: /4mentioning
confidence: 99%
“…[ 2 3 ] In a review by Khater and Sakr in 2013, there were only 250 cases previously reported and since then six more cases were reported. [ 2 5 6 7 8 9 ] There is a female preponderance (70%), and this pathology affects those in their third to sixth decades, with a mean age of 44 years. [ 2 6 7 ] However, there are cases described in younger patients, as is the case with our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Even though no pathophysiological components have been portrayed to explain the development of this tumor, it may be related to an endocrine shift. 1,2 Here, we report the case of a senior woman who primarily presented with abdominal pain and vaginal bleeding. She complained of frequent urination, pelvic pain, and a feeling of pelvic pressure.…”
Section: Introductionmentioning
confidence: 99%